TEACHING APPROACHES WHEN WORKING WITH STUDENTS WITH LOW SOCIO-ECONOMIC STATUS: DO TEACHERS GIVE STUDENTS AUTONOMY TO LEARN? - Česnavičienė, Jūratė; Brandišauskienė, Agnė; Bruzgelevičienė, Ramutė Teresė; Nedzinskaitė-Mačiūnienė, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
As PISA 2018 results show (OECD, 2018, 2019), students with high SES achieve better results in all countries than their peers with low SES. The impact of personal background circumstances on student performance is partly mediated by other factors, e.g. students’ access to educational resources, differences in the opportunity to learn, and grade repetition and tracking. Meanwhile, Jensen (2009) claims that the major factor affecting the achievement of students living in unfavourable conditions is not their living environment, but rather the school and the teachers. Jensen (2013) notes that the best strategy to help students with low SES achieve success in learning is to provide such conditions that they are involved in the learning process. Therefore, the present article explores how teachers employ self-determination theory when working with students with low SES. The participants in the quantitative survey were selected from five schools of one District Municipality in Lithuania characterized by low SES. The sample consisted of 95 teachers and 183 students. The results concerning the teachers demonstrate that the teachers working with low-SES status students have the moderately autonomy-supportive style, yet they tend to employ the controlling motivating style alongside the autonomy-supportive one. In the students’ opinion, they have a fairly close relationship with their teachers and feel understood by them. The students also maintain that the teachers give them choices, encourage them to ask questions and express confidence in their abilities. However, it can be determined that the teachers rarely seek to empower children to learn independently.